PENGARUH PERTUMBUHAN EKONOMI SEKTOR INDUSTRI DAN TINGKAT PENDIDIKAN TERHADAP PENYERAPAN TENAGA KERJA PADA SEKTOR INDUSTRI DI PROVINSI BANTEN - Sayifullah Sayifullah; Ade Supriatna (FEB Universitas Sultan Ageng Tirtayasa, 2017)
Banten Province is one province that has an industrial area that is pretty much like the Cilegon, Serang and Tangerang regency. For the expansion of employment, the industrial sector is expected to absorb more labor than other sectors. This study aims to determine how the influence of both partially and simultaneously economic growth variables and variable levels of industry sectors that include resident education with graduate elementary, junior high, high school, and higher education on employment in the industrial sector in the province of Banten. This study uses secondary data consisting of the data years 2005-2011 were obtained from Statistics Province. This study analyzes the method using Fixed Effect Model on Panel Data. Results of analysis of this study it can be concluded that the variables of economic growth and industrial sector levels elementary, junior high, high school and PT simultaneously have a positive and significant impact on employment in the industrial sector. F-calculated value of 538.1693 with a probability value of 0.000000 is smaller than alpha 5 percent, so it can be concluded that there is significant influence between the variables of economic growth in the industrial sector and the education level of the labor market in the industrial sector. R2 value of 0.994273 indicates that 99.4273% of independent variables to explain the dependent variabel